Effects of unsaturated fatty acid methyl esters on the oxidation stability of biodiesel determined by gas chromatography-mass spectrometry and information entropy methods. (September 2021) - Wang, Wenchao; Liu, Huili; Li, Fashe; Wang, Hua; Ma, Xin; Li, Jingjing; Zhou, Li; Xiao, Quan
Abstract: To explore the trend of fatty acid methyl esters (FAMEs) during the oxidation process of biodiesel, this study uses gas chromatography - mass spectrometry (GC-MS) combined with information entropy theory to propose a new method to analyze the effect of FAMEs on the stability of biodiesel (especially with different amounts of unsaturated FAMEs). The induction periods of the main FAMEs in biodiesel were determined by the Rancimat method. The results showed that the longest induction period of methyl stearate was 248 h, while the induction of methyl linoleate was only 0.12 h. Accelerated oxidation of biodiesel, using GC-MS analysis showed that the oxidation trends of FAMEs was different. The oxidation rate of methyl linoleate was the fastest. A mathematical equation was proposed to calculate the trend of FAMEs. The results showed that during the 5 h accelerated an oxidation process, the content of methyl linoleate decreased from 28.35% to 2.10%, while the content of methyl oleate decreased by 18.21%. Using information entropy, the weighting coefficients of FAMEs in the oxidation process of biodiesel were calculated. The weighting coefficient of methyl linoleate was as high as 0.6797. Methyl linoleate was the main reason why biodiesel was easily oxidized. Highlights: GC-MS and information entropy methods was employed for FAMEs oxidation evaluation. The weight coefficients of different FAMEs in the oxidation process are obtained. Methyl linoleate is the main internal reason that affects the oxidation of biodiesel.